OPTIMIZATION OF SECRETOLYTIC TREATMENT OF ACUTE SINUSITIS - S.V. Makarevich ("Paediatrician" Publishers LLC, 2008)
Efficiency of sinupret in children with acute sinusitis as a drug with serolytic action, is studied. it is established that secretolytic therapy in case of acute sinusitis, aimed at the improvement of drainage and ventilation function of paranasal sinuses, is one of the potentially productive directions of nonbinvasive methods of treatment of acute sinusitis.Key words: children, acute sinusitis, secretolytic treatment.